2022
DOI: 10.1016/j.celrep.2022.110304
|View full text |Cite
|
Sign up to set email alerts
|

Histone chaperone FACT complex coordinates with HIF to mediate an expeditious transcription program to adapt to poorly oxygenated cancers

Abstract: Highlights d Cancer cells rely on the FACT complex to survive under hypoxic stress d PHD/VHL axis regulates the protein stability of the FACT complex d The FACT complex enables HIF-mediated metabolic reprogramming in cancer cells d Targeting the FACT complex is an effective therapeutic approach for hypoxic tumors Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…( A ) Potential implication of FACT complex in NRF2/KEAP1 pathway. FACT complex works in tandem with NRF2, establishing a positive feedback loop to over-express antioxidant proteins [ 31 ]. ( B ) A potential implication of the FACT complex in the ATR/CHK1 pathway is to prevent replication stress in response to DNA damage [ 22 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( A ) Potential implication of FACT complex in NRF2/KEAP1 pathway. FACT complex works in tandem with NRF2, establishing a positive feedback loop to over-express antioxidant proteins [ 31 ]. ( B ) A potential implication of the FACT complex in the ATR/CHK1 pathway is to prevent replication stress in response to DNA damage [ 22 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Defining the FACT complex as a novel target for cancer treatment enabled researchers to investigate Curaxin as a therapeutic treatment for HCC patients [ 32 ]. Curaxin, a small molecular inhibitor of FACT that induces chromatin trapping of FACT and significantly inhibits normal human FACT activities, causes intracellular acidification and apoptosis of cancer cells [ 31 , 33 ]. Curaxin treatment has been shown to block the gene expressions needed for oxidative stress and hypoxia responses in HCC cells, presumably in correlation with the FACT complex’s interaction with NRF2 [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Under hypoxic conditions, HIF‐1α and HIF‐2α exhibit robust expression in HCC; these expression patterns contribute to increased production of angiogenic factors, such as vascular endothelial growth factor (VEGF), to drive angiogenesis 101 . Hypoxia‐inducible factor 1 (HIF‐1), a transcription factor that rapidly activates a range of gene transcription, can ensure the survival of cancer cells in hypoxia and further imbue cancer cells with aggressive properties (self‐renewal, metastasis, angiogenesis and treatment resistance) 102 . Sorafenib‐focused studies have shown that hypoxic can induce sorafenib resistance, and HIF‐1a or HIF‐2α inhibitors with different mechanisms can improve outcomes 101,103–105 .…”
Section: Possible Mechanisms Of Resistance To Lenvatinibmentioning
confidence: 99%
“…101 Hypoxia-inducible factor 1 (HIF-1), a transcription factor that rapidly activates a range of gene transcription, can ensure the survival of cancer cells in hypoxia and further imbue cancer cells with aggressive properties (self-renewal, metastasis, angiogenesis and treatment resistance). 102 Sorafenib-focused studies have shown that hypoxic can induce sorafenib resistance, and HIF-1a or HIF-2α inhibitors with different mechanisms can improve outcomes. 101,[103][104][105] Hypoxia is also strongly associated with the lenvatinib response in HCC.…”
Section: Hypoxiamentioning
confidence: 99%
“…This suggests that it may be interesting to try CBL0137 in combination with ICB, which can be enhanced by innate immune activation, including IFNg [ 296 ]. Finally, FACT has been demonstrated to mediate adaptation to hypoxia and CBL0137 impaired tumor growth and enhances the effects of an anti-angiogenic drug, bevacizumab, in a hepatocellular carcinoma model [ 297 ]. While the effects of CBL0137 have not been reported in PCa, it has entered clinical trials for a number of other cancer types, and its potential to enhance genotoxic agents, impair transcription, sensitize hypoxic cells, and improve DDR inhibitor and ICB responses may be useful to explore in future work (NCT01905228, NCT02931110, NCT03727789, NCT05498792, NCT04870944).…”
Section: Emerging Targets In Crpcmentioning
confidence: 99%